2020
DOI: 10.1097/htr.0000000000000550
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Secondary ADHD on Long-Term Outcomes After Early Childhood Traumatic Brain Injury

Abstract: Objective: To examine the impact of secondary attention-deficit/hyperactivity disorder (SADHD) on long-term global and executive functioning in adolescents after traumatic brain injury (TBI). Setting: Three tertiary cared children's hospitals and 1 general hospital. Participants: One hundred twenty children (TBI: n = 54; orthopedic injury: n = 66) without preinjury ADHD evaluated approximately 6.8 years post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 56 publications
2
14
0
Order By: Relevance
“…Long term follow up studies examining EF outcomes from 3 to 10 years after injury have also shown persistent problems, with EFs not returning to pre-injury levels ( 35 , 62 64 ). Executive dysfunction after TBI has serious consequences for post-traumatic adjustment ( 65 ) and contributes to poorer educational outcomes ( 66 , 67 ) and reduced social competence ( 68 ). TBI may exacerbate pre-existing EF problems in children and may magnify vulnerability to an array of poorer outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Long term follow up studies examining EF outcomes from 3 to 10 years after injury have also shown persistent problems, with EFs not returning to pre-injury levels ( 35 , 62 64 ). Executive dysfunction after TBI has serious consequences for post-traumatic adjustment ( 65 ) and contributes to poorer educational outcomes ( 66 , 67 ) and reduced social competence ( 68 ). TBI may exacerbate pre-existing EF problems in children and may magnify vulnerability to an array of poorer outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Neurocognitive impairments and behavioral abnormalities have been consistently observed in children with TBI (Konigs et al, 2015;Poslinder et al, 2015;Dewan et al, 2016;Lumba-Brown et al, 2018). Among the most common cognitive consequences, significant attention deficits were reported in about 35% of children within two years of their TBI (Max et al, 2005), and were observed to strongly contribute to elevated risk for severe psychopathology and impairments in overall functioning in late adolescence, with the pathophysiological underpinning yet to be fully elucidated (Le Fur et al, 2019;Narad et al, 2019). The post-TBI attention problems in children have been evaluated and treated based on endorsements of behavioral symptoms from subjective observations, and have resulted in largely divergent results regarding effectiveness (Backeljauw and Kurowski, 2014;Kurowski et al, 2019;LeBlond et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…When analyzing the coverage in the modern literature of extracranial complications of TBI, most of the sources we have encountered describe changes in the organs in moderate and severe TBI [ 51 , 52 , 53 ]. Simultaneously, changes in cognitive functions and psycho-emotional state are mainly described in mild TBI [ 54 , 55 , 56 ]. Our results signalto search for a possible connection between the pathology of the internal organs and previous TBI in children and adolescents, even with a mild TBI.…”
Section: Discussionmentioning
confidence: 99%